2018
DOI: 10.1038/s41598-018-25668-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphoregulatory functions of the RNA-binding motif protein 3 in cell spreading, polarity and migration

Abstract: RNA-binding proteins are emerging as key regulators of transitions in cell morphology. The RNA-binding motif protein 3 (RBM3) is a cold-inducible RNA-binding protein with broadly relevant roles in cellular protection, and putative functions in cancer and development. Several findings suggest that RBM3 has morphoregulatory functions germane to its roles in these contexts. For example, RBM3 helps maintain the morphological integrity of cell protrusions during cell stress and disease. Moreover, it is highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 111 publications
1
13
0
Order By: Relevance
“…Higher Rbm3 expression was confirmed by qPCR, western blot analysis and immunohistochemistry (Figure 6B–E and Figure S13). RBM3 has been reported to be involved in carcinogenesis [28,29]. Data from the TIGER-LC and TCGA showed a similar expression pattern for Rbm3 in adjacent human liver, HCC and ICC samples, respectively, when compared to our murine data (Figure 6F,G).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Higher Rbm3 expression was confirmed by qPCR, western blot analysis and immunohistochemistry (Figure 6B–E and Figure S13). RBM3 has been reported to be involved in carcinogenesis [28,29]. Data from the TIGER-LC and TCGA showed a similar expression pattern for Rbm3 in adjacent human liver, HCC and ICC samples, respectively, when compared to our murine data (Figure 6F,G).…”
Section: Resultssupporting
confidence: 80%
“…Rbm3 was also upregulated in two independent cohorts of human liver carcinomas, especially in ICCs. RBM3 has been reported to promote the development of colitis-associated cancer or enhance migration ability in neuroblastoma cell lines [28,29]. In addition, high RBM3 levels were significantly associated with reduced overall survival in pancreatic cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…RBM3 is a member of the cold-shock protein family that regulates mRNA metabolism and has pleiotropic effects in cellular stress and oncogenesis (46). RBM3 protein is rarely overexpressed in normal tissues, but it is overexpressed in some solid tumors and, in recent studies, its expression levels seem to be related to prognosis and cytostatic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that RBM3 mediates the protective effects of hypothermia in brain slices ( Chip et al, 2011 ). Furthermore, RBM3 is known to increase global protein synthesis rates ( Dresios et al, 2004 ), particularly in dendrites ( Smart et al, 2007 ) and to regulate neuronal polarity ( Pilotte et al, 2018 ) and neurogenesis during development ( Xia et al, 2018 ), which may contribute to its effects on structural plasticity.…”
Section: Introductionmentioning
confidence: 99%